TRADISI PESANTREN SEBAGAI PUSAT PERADABAN MUSLIM NUSANTARA - Cholid Abdullah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2014)
Pesantren (Islamic boarding school) with its typology hasgiven effect to the civilization in Indonesia. Pesantren in Indonesiaplays three important roles in Islamic civilization. First, pesantrenserves as center of religious study that creates muslim scholars, so thatthey will develop Islamic teachings. Second, the act of openness to themodernization by considering about the act of selectivity that functionsas a filter. Third, pesantren creates a link to connect among religion,culture and local wisdom.